Outcome of diaphragmatic herniation and eventration repair in adults - Khakural, Prabhat; Sapkota, R; Sayami, P (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Diaphragmatic hernia and eventration are amongst the less commonly encountered thoracic surgical problems in Nepal. Unlike, the cases of traumatic herniation, adults with congenital hermination and eventration seek medical attention very late. Methods: It is a retrospective observational study of patients presenting with diaphragmatic hermiation and eventration at Manmohan Cardiothoracic Vascular and Transplant Center, Kathmandu, Nepal. Medical records of five years (May, 2010 to April, 2015) were reviewed. Analysis of the demographic profile, clinical features, management and outcome was done. Results: There were a total of 15 patients who were diagnosed to have diaphragmatic hermiation and eventration. There were eight cases of hermiation and seven cases of eventration. There were three cases of acute diaphragmatic hermiation. Thoracic trauma was found to be associated in three cases of herniation only. The mean age at presentation was 46.5 years. Thoracic trauma was seen in Younger age (mean age being 34 yrs). There were two cases of morgagni hernia and one of these was diagnosed incidentally. Mean duration of symptoms was two months. The most common presenting symptoms were shortness of breath and cough. Twelve cases were repaired via thoracotomy. Mean size of diaphragmatic defect was six centimeters. The most commonly herniated organ was stomach followed by momentum. Placation was the most commonly performed procedure in eventration and primary repair was done in six cases of hermiation and mesh repair in two cases. Only two patients had superficial surgical site infection. Mean duration of hospital stay was eight days. The patients were doing good up to mean follow up period of four months. Conclusion: Diaphragmatic hermiation and eventration in symptomatic patients should be managed surgically. Surgical approaches can be thoracotomy, laparotomy and Video Assisted Thoracoscopic Surgery. Outcome following surgery is good with minimal postoperative complications. JSSN 2015; 18 (1), Page : 1-4